2023
DOI: 10.3389/fimmu.2023.1220165
|View full text |Cite
|
Sign up to set email alerts
|

Combination of thalidomide and Clostridium butyricum relieves chemotherapy-induced nausea and vomiting via gut microbiota and vagus nerve activity modulation

Abstract: Nausea and vomiting (CINV) are distressful and widespread side effects of chemotherapy, and additional efficient regimens to alleviate CINV are urgently needed. In the present study, colorectal cancer (CRC) mice model induced by Azoxymethane (AOM)/Dextran Sodium Sulfate (DSS) was employed to evaluate the cancer suppression and CINV amelioration effect of the combination of thalidomide (THD) and Clostridium butyricum. Our results suggested that the combination of THD and C. butyricum abundantly enhanced the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Recent studies have fully demonstrated that the vagus nerve regulates emotions and behavior by influencing CNS responses ( Fulling et al., 2019 ). The disconnection of vagus nerve can block the central signaling in species belonging to the Lactobacillus and Bifidobacterium genera, resulting in impaired emotional regulation ( Zhao et al., 2023 ). In summary, the vagus nerve plays an indispensable role in the information transmission of gut microbiota and CNS.…”
Section: Signaling Mechanisms Of Microbiota Gut Brain Axis Communicationmentioning
confidence: 99%
“…Recent studies have fully demonstrated that the vagus nerve regulates emotions and behavior by influencing CNS responses ( Fulling et al., 2019 ). The disconnection of vagus nerve can block the central signaling in species belonging to the Lactobacillus and Bifidobacterium genera, resulting in impaired emotional regulation ( Zhao et al., 2023 ). In summary, the vagus nerve plays an indispensable role in the information transmission of gut microbiota and CNS.…”
Section: Signaling Mechanisms Of Microbiota Gut Brain Axis Communicationmentioning
confidence: 99%